"Hands-on" plus "inquiry"? Effects of withholding answers coupled with physical manipulations on students' learning of energy-related science concepts. (April 2019) - Zhang, Lin
Abstract: A recent discussion on science teaching has been focusing on questions of whether it is necessary to withhold answers from learners until inquiry activities are completed and whether learners develop high-level science learning when they are physically involved in scientific investigations. To contribute to this topic, the present study examined the effects of withholding answers from learners coupled with involving them in physical manipulations on their learning of energy transfer in three domains, knowing, reasoning, and applying. The study compared students' learning outcomes in the hands-on inquiry condition that incorporated the two instructional elements, with learning in the explicit investigation condition that only involved learners in manipulations, and in direct instruction condition that excluded the two instructional elements. The results showed that the instructional conditions affected students' learning of energy transfer in knowing and reasoning, but not in applying. After controlling for students' prior knowledge, participants in the hands-on inquiry condition gained less class content and demonstrated a lower ability of reasoning than those in the direct instruction condition. Students did not differ in their ability to apply the learned content to real-life situations across conditions. Highlights: This study empirically examined effects of withholding answers + involving physical manipulations on students' learning. This study focused students' learning outcomes on three domains, knowing, reasoning, and applying. Withholding answers coupled with involving manipulations led to less gain in class content and lower ability in reasoning. There was no difference in applying across conditions.